Midwifery students experience of continuity of care: A mixed methods study. (July 2021) - Foster, Wendy; Sweet, Linda; Graham, Kristen
Abstracts: Background: Continuity of Care Experiences are a mandated component of Australian midwifery programs leading to registration. Despite research evidence of the benefits of Continuity of Care Experiences for student learning and for women, there is limited evidence on the personal impact of this experience to students. Additionally, there is limited guidance on how to best support students to successfully complete this valuable component of their program. Objective: To identify the emotional, psychological, social and financial costs of undertaking the Continuity of Care Experience component of a midwifery program and to provide information which may lead to educational strategies within CoCE aimed to improve student support and alleviate challenges. Design: Using surveys and diary entries, a convergent parallel mixed methods approach was used to collect qualitative and quantitative data concurrently. Descriptive statistics were used to analyse financial cost, and clinical, travel and wait times. A constant comparative analysis was used for qualitative data about student's Continuity of Care Experiences. Integrative analysis was used to reconstruct the two forms of data. Setting: Two Australian universities offering Bachelor of Midwifery programs. Participants: Seventy students completed the demographic survey and 12 students submitted 74 diaries describing 518 episodes of care. There was a response rate of 18% recorded. Findings: Analysis identified four themes: perception of Continuity of Care Experiences; personal safety; impact on self and family; and professional relationships. The mean time spent per completed experience was 22.20 hours and the mean cost was 367.19. Although students found Continuity of Care Experiences to be a valuable learning experience, they identified numerous factors including time, money, and personal circumstances that impacted on their ability to successfully meet the requirements. Implications for practice: Continuity of Care Experiences are a highly valuable, but often challenging component of midwifery education in Australia. Using a model of social interdependence, students, educators and maternity care providers may engage better with the process and philosophies of CoCE.